(untitled) (Journal of the College of Basic Education, 2022)
The research provides an analysis of Turkish maritime policy in the eastern Mediterranean and its extent the effectiveness of this policy for Turkish interests with an indication of the most important problems and challenges facing these Interests. This policy delineates geographical dimensions that take a political character, which imposes on the state to follow A specific policy that guarantees its national interests, and it is a multidimensional policy that stems from centralization Turkey’s strength and that this force enables it to implement a new policy in the eastern Mediterranean Its geographical location gives it a great opportunity for movement and maneuver on the regional level. National interests are an analytical tool for state behavior, because these interests direct the state’s behavior in most cases, the state needs to redefine its interests and change its priorities accordingly for its capabilities. Turkey has very much welcomed the developments that took place in Libya after 2011, and its interest increased Its interests and influence have expanded in it, in order to achieve all of the goals that it aspires to Turkey to serve its interests. Libya and its geopolitical characteristics are represented in its geographical location and possession A long coast on the Mediterranean Sea and its containment of great and varied natural resources made it A country that occupies an important position in the Turkish decision-maker as a country possessing the specifications Geography that serves Turkish interests.